2018
DOI: 10.1128/mcb.00303-18
|View full text |Cite
|
Sign up to set email alerts
|

So Many Roads: the Multifaceted Regulation of Autophagy Induction

Abstract: Autophagy is an evolutionary conserved, degradative process from single-cell eukaryotes, such as , to higher mammals, such as humans. The regulation of autophagy has been elucidated through the combined study of yeast,, mice, , and humans. MTOR, the major negative regulator of autophagy, and activating nutrient kinases, such as 5'-AMP-activated protein kinase (AMPK), interact with the autophagy regulatory complex: ULK1/2, RB1CC1, ATG13, and ATG101. The ULK1/2 complex induces autophagy by phosphorylating downst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
89
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 88 publications
(103 reference statements)
1
89
0
Order By: Relevance
“…AMPK phosphorylates and controls important upstream regulators of the autophagic cascade, including the ULK1 and the VPS34-dependent PI3K complexes that govern initial steps in the formation of phagophores giving rise to autophagosomes [9][10][11] . However, the molecular mechanisms of autophagy regulation are not fully resolved and may not be linear 40 . With Cyclin Y/CDK16 we have identified an additional effector of AMPK.…”
Section: Articlementioning
confidence: 99%
“…AMPK phosphorylates and controls important upstream regulators of the autophagic cascade, including the ULK1 and the VPS34-dependent PI3K complexes that govern initial steps in the formation of phagophores giving rise to autophagosomes [9][10][11] . However, the molecular mechanisms of autophagy regulation are not fully resolved and may not be linear 40 . With Cyclin Y/CDK16 we have identified an additional effector of AMPK.…”
Section: Articlementioning
confidence: 99%
“…Phosphorylation on Ser750 residue of ULK2 by SGK1 (as its authentic substrate protein) is also one of regulatory points to activate its autophagy functions. It has been reported that mTOR1 phosphorylation on Ser729 in (kavlftvgSpphs) of ULK2 also enhances ULK2's autophagy activity [1] [2] [3] [4].…”
Section: Discussionmentioning
confidence: 99%
“…Uncoordinated 51-like kinase 2 (ULK2), like ULK1, is a member of the serine/threonine kinase protein family that plays an essential role in the regulation American Journal of Molecular Biology of autophagy in mammalian cells. ULK2 is expressed ubiquitously [1] [2] [3] [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mammalian target of rapamycin (mTor) kinase is an important regulator of autophagy induction where active mTOR suppresses autophagy while inhibition of mTOR activity promotes autophagy onset (Rabinowitz and White, 2010), although a growing number of examples of mTOR-independent autophagy induction have been reported providing the notion that autophagy induction is not a single linear process but can rather be induced through the action of multiple interconnected key regulators (Corona Velazquez and Jackson, 2018). While autophagy is largely a cytoplasmic event, recent studies have focussed on the nuclear transcription factors and epigenetic marks that modulate the expression of various autophagic components (reviewed in Fullgrabe et al (2014)).…”
Section: Introductionmentioning
confidence: 99%